Endovascular Treatment of Pulmonary Artery Pseudoaneurysms Post-COVID-19 Pneumonitis - Nischal G. Kundaragi; Sunil Kumar K.; Rahul Talwade; Srivatsa Lokeshwaran; Priyanka V. K. (Journal of Clinical Interventional Radiology ISVIR)
Pulmonary artery pseudoaneurysms (PAPs) are uncommon entities consisting of contained rupture of the pulmonary artery and are a potentially fatal cause of hemoptysis. We describe two index cases of left lower lobe PAPs and arterial ectasia post-COVID-19 pneumonitis and their endovascular treatment with Amplatzer vascular plug, coils, and glue.